Left atrial appendage aneurysm in pediatrics: Case study and literature review - Norozi, Kambiz; Subasri, Mathushan; Diaz, Luis Altamirano; Honjo, Osami (Frontiers in Cardiovascular Medicine, 2023)
Left atrial appendage aneurysm (LAAA) is a rare cardiac pathology that is often identified in adulthood. There are a myriad of presentations related to atrial appendage enlargement, but most are asymptomatic. Pediatric cases of LAAA are extremely rare. We report a case of an incidental giant LAAA found in a healthy 6-year-old boy. He was successfully treated with surgical resection. A review of the literature shows that the presentation of LAAA in pediatrics likely involves cardiac or respiratory symptoms but can also be incidental findings. Similar to adults, diagnosis requires cardiac imaging, with echocardiography being the mainstay. Surgical intervention is indicated in symptomatic and most asymptomatic patients to prevent complications. More research is warranted into the optimal timing of surgery and alternative surgical approaches for complex cases.